Perubahan Budaya dalam Ritus Pasca Panen Padi: (Analisis Perubahan Sosial dalam Dimensi Kultural dan Dampaknya Terhadap Pertumbuhan Ekonomi Kabupaten Tabanan) - Ni Putu Sri Pratiwi; Nunung Nurwati (Jayapangus Press, 2023)
The purpose of this study is to explain the social changes that occur in the cultural dimension of post-harvest rites in Tabanan Regency and their impact on economic growth in Tabanan Regency. The reason for this case being chosen is because the agricultural cultural rites in Bali have experienced many shifts, but no one has conducted research regarding the changes that have occurred from the post-harvest rites by comparing their implementation in the past with the present. This research uses qualitative methods, data collection techniques use literature studies and in-depth interviews where the meta data is taken from books, online journals, and other references as well as the results of interviews with several informants consisting of traditional leaders, the people of Tabanan Regency who are still farming, and assistants regent of Tabanan. This research is analyzed using the concept of social change in the cultural dimension put forward by Himes & Moore by looking at the forms of integration that occur, as well as changes in the dimensions of time, process and impact. The results of the study showed that there was a change in the form of the post-rice harvest rite which was originally complex, now it becomes simpler by removing some of the elements in it. Nevertheless, these changes have had a good impact on economic growth in Tabanan Regency.